Impacts of bt brinjal (eggplant) technology in Bangladesh - Ahmed, Akhter; Hoddinott, John F.; Islam, Kazi M. S.; Rahman Khan, A. S. M. M.; Abedin, Naveen; Hossain, Nusrat Z.; Ghostlaw, Julie; Parvin, Aklima; Quabili, Wahid; Rahaman, S. M. Tahsin; Rahman, Waziha; Redoy, Md.; et al. (United States Agency for International Development, 2019)
This study examines the impact of genetically modified (GM) eggplant in Bangladesh. Eggplant, called brinjal in Bangladesh, is a high-value crop that is widely grown and consumed. Brinjal is highly vulnerable to fruit and shoot borer (FSB) pest. In response, farmers spray the crop heavily and repeatedly with highly toxic pesticides but with limited success. Over a 10-year period, public sector Bangladeshi agricultural researchers, with support from Maharashtra Hybrid Seeds Co. Pvt. Ltd. (Mahyco) and researchers based in the United States, have developed a series of GM varieties of Bt brinjal that are resistant to FSB. Extensive biosafety work has demonstrated that there are no significant differences between Bt brinjal and its non-GM counterparts (APAARI 2018). Following regulatory review, Bangladesh approved Bt brinjal for human consumption (APAARI 2018). Other studies suggest that these varieties convey higher yields with lower applications of pesticides. The introduction of GM crops remains controversial in Bangladesh and globally. Frequent criticisms include claims that they are harmful to the environment, damaging to human health, and inaccessible to small farmers for cost or intellectual property reasons. It is also claimed that GM crops (including Bt brinjal) convey no yield benefits, with critics noting that much of the work on economic benefits was based on observational data rather than randomized controlled trials (RCTs). Furthermore, research on GM crops is perceived to be industry-influenced or biased in some way.